Hydrous Ferric Oxides in Sediment Catalyze Formation of Reactive Oxygen Species during Sulfide Oxidation - Murphy, Sarah A.; Meng, Shengnan; Solomon, Benson M.; Dias, Dewamunnage M. C.; Shaw, Timothy J.; Ferry, John L. (Frontiers in Marine Science, 2016)
Abstract: This article describes the formation of reactive oxygen species as a result of the oxidation of dissolved sulfide by Fe(III)-containing sediments suspended in oxygenated seawater over the pH range 7.00 and 8.25. Sediment samples were obtained from across the coastal littoral zone in South Carolina, US, at locations from the beach edge to the forested edge of a Spartina dominated estuarine salt marsh and suspended in aerated seawater. Reactive oxygen species (superoxide and hydrogen peroxide) production was initiated in sediment suspensions by the addition of sodium bisulfide. The subsequent loss of HS-, formation of Fe(II) (as indicated by Ferrozine), and superoxide and hydrogen peroxide were monitored over time. The concentration of superoxide rose from the baseline and then persisted at an apparent steady state concentration of approximately 500 nanomolar at pH 8.25 and 200 nanomolar at pH 7.00 respectively until >97% hydrogen sulfide was consumed. Measured superoxide was used to predict hydrogen peroxide yield based on superoxide dismutation. Dismutation alone quantitatively predicted hydrogen peroxide formation at pH 8.25 but over predicted hydrogen peroxide formation at pH 7 by a factor of approximately 102. Experiments conducted with episodic spikes of added hydrogen peroxide indicated rapid hydrogen peroxide consumption could account for its apparent low instantaneous yield, presumably the result of its reaction with Fe(II) species, polysulfides or bisulfite. All sediment samples were characterized for total Fe, Cu, Mn, Ni, Co and hydrous ferric oxide by acid extraction followed by mass spectrometric or spectroscopic characterization. Sediments with the highest loadings of hydrous ferric oxide were the only sediments that produced significant dissolved Fe(II) species or ROS as a result of sulfide exposure.